Histone chaperone Spt6 is required for class switch recombination but not somatic hypermutation - Okazaki, Il-mi; Okawa, Katsuya; Kobayashi, Maki; Yoshikawa, Kiyotsugu; Kawamoto, Shimpei; Nagaoka, Hitoshi; Shinkura, Reiko; Kitawaki, Yoko; Taniguchi, Hisaaki; Natsume, Tohru; Iemura, Shun-Ichiro; Honjo, Tasuku (Proceedings of the National Academy of Sciences - PNAS, 2011)
Activation-induced cytidine deaminase (AID) is shown to be essential and sufficient to induce two genetic alterations in the Ig loci: class switch recombination (CSR) and somatic hypermutation (SHM). However, it is still unknown how a single-molecule AID differentially regulates CSR and SHM. Here we identified Spt6 as an AID-interacting protein by yeast two-hybrid screening and immunoprecipitation followed by mass spectrometry. Knockdown of Spt6 resulted in severe reduction of CSR in both the endogenous Ig locus in B cells and an artificial substrate in fibroblast cells. Conversely, knockdown of Spt6 did not reduce but slightly enhanced SHM in an artificial substrate in B cells, indicating that Spt6 is required for AID to induce CSR but not SHM. These results suggest that Spt6 is involved in differential regulation of CSR and SHM by AID.